Colonial Republic of Chile 1929-1973. Escuela e invisibilización del mapun-kimun del pueblo nación mapuche - Mansilla Sepúlveda, Juan (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the study is to analyze the implications that the State of Chile has had in its consolidation in Mapuche’s territory after the occupation of the Wajmapu, where the Chilean school has been a determining control device to establish a monocultural educational regime that made the Mapuche people's mapunkimun invisible. Originality: The idea of ​​a colonial republic in Chile is not developed in the education history, where the effects of state violence are reconstructed in an asymmetric intercultural relations framework. Method is a qualitative research work, with descriptive scope through a documentary study design, which, using work strategies with primary and secondary sources, allowed the systematic review of the documentary corpus. The conclusions show the recognition of the role that the school played to achieve monoculturalism and installation of Western knowledge. However, from a long-term cultural history, the school as a state agency did not achieve its mission, because the mapun-kimun of the Mapuche state people survived all control devices and attempts at submission and today maintains that cultural resistance in a state that continues to operate from a logic that excludes the ethnical and linguistic diversity.